Variation in parental experiences with their child's hospitalization over the COVID-19 pandemic - Kyle A. Kemp; Paul Fairie; Brian Steele; Maria J. Santana (SpringerOpen, 2023)
Abstract Background Hospitals and healthcare workers have been greatly impacted by the COVID-19 pandemic. The potential impacts upon the patient experience have been less documented, particularly in the pediatric setting. Our aim was to examine how parental experiences with their child's hospitalization varied during the COVID-19 pandemic at two children's hospitals in Alberta, Canada. Methods A random sample of parents were surveyed within six weeks of their child's discharge from Alberta's two children's hospitals. Surveys were administered using the Alberta Pediatric Inpatient Experiences Survey (APIES) - a validated instrument used to assess parental experiences during their child's hospitalization. Surveys were linked with administrative inpatient records. Three cohorts were created based on hospital discharge date: Pre-COVID (Pre: April 2019 to March 2020), COVID year one (C1: April 2020 to March 2021), and COVID year two (C2: April 2021 to March 2022). We examined 48 survey questions, including four overall rating scales. Survey responses were Likert scales. These were transformed to normalized scores from 0 (worst) to 100 (best). Differences between cohorts were assessed using ANOVA and the post-hoc Tukey test. Results A total of 3,611 surveys (1,314 Pre; 997 C1; 1,300 C2) were completed over the three-year period. Five questions showed differences between the Pre and C1 periods, six showed differences between Pre and C2, and 13 showed differences between C1 and C2. Among these questions, scores pre-COVID were lower than COVID year one, while results in COVID year two were lower than pre-COVID and COVID year one. Thirty-one survey questions showed no statistical differences between the three time periods. For the overall ratings, only hospital rating showed a difference in any of the periods (91.4 C1 vs. 90.2 C2). Overall ratings of doctors, nurses, and recommendation of the hospital to others showed no differences. Conclusion This study showed that the experiences of parents during the first year of the COVID-19 pandemic were mildly better or comparable to historical results. This changed over the following year, where lower scores were reported on 13 questions.